The use of information technology of eaudit system on audit quality - Ida Farida, Taufiq Supriadi, Mulyani.S, Eddy Mulyadi Soepardi (Opción, 2019)
This research was conducted to determine an effect of the use ofinformation technology and successful implementation of e-auditsystems on audit quality via descriptive and verificative statisticalanalysis using statistical tool. As a result, the use of informationtechnology does not affect audit quality while the successfulimplementation of e-audit systems have an effect on audit quality. Inconclusion, the successful implementation of the e-audit system onAudit Quality has not been fully qualified as the implementation of thee-audit system is reflected by the efficiency and effectiveness of theinspection process.